Integrasi Business Model Canvas (BMC) dengan Strategi Keuangan dan Perpajakan pada UMKM di Kecamatan Simokerto - Adrianto Trimarjono; Wiwin Wahyuni; Lilik Mardiana (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The challenges faced by MSMEs in Indonesia, especially in Surabaya, often revolve around business management, finance, and taxation. One potential solution is the integration of the Business Model Canvas (BMC) with financial and tax strategies, which can help MSMEs streamline their operations. The Business Model Canvas (BMC) training program is designed to assist MSMEs in reorganizing their business models and implementing new strategies that address key operational challenges. This program also incorporates financial and tax considerations, helping MSMEs manage their finances more effectively and comply with tax regulations. With this approach, MSMEs are expected to improve their operational efficiency, enhance tax compliance, and strengthen their competitive edge in the market. The method involves direct engagement with MSMEs through hands-on workshops and personalized mentoring sessions. This initiative is set to take place in May 2025, offering MSMEs valuable tools to enhance their business practices, optimize financial management, and foster long-term growth and success in the market.